Petrophysical evaluation of sandstone reservoir of well E-AH1, E-BW1 and E-L1 Central Bredasdorp Basin, offshore South Africa - Magoba, Moses (University of the Western Cape, 2015)
Magister Scientiae - MSc === The Bredasdorp basin is a sub-basin of the greater Outeniqua basin. It is located off the south coast, Southeast of Cape Town, South Africa. This basin is one of the largest hydrocarbon (mainly gas) producing basins within Southern Africa. The petrophysical characteristic of the E-block sandstone units within the Bredasdorp basin has been studied to evaluate their hydrocarbon potential. The data sets used in this research were wireline logs (Las format), core data, and geological well completion reports. The three studied wells are E-AH1, E- BW1 and E-L1. The evaluated interval ranges from 2000.33m to 3303.96m in depth with reference to Kelly bushing within the wells. The sandstone reservoirs of the Bredarsdorp basin are characterized by a range of stacked and amalgamated channels. They originated from materials eroded from pre-existing high stand shelf sandstone and transported into the central Bredarsdorp basin by turbidity current. These sandstones are generally in both synrift and drift section. The basin is thought to have developed from fan deltas and stream overwhelmed to water dominated delta. River dominated deltaic system progresses southward over the Northern edge of the central Bredasdorp basin. The Interactive Petrophysics (IP) software has been used extensively throughout the evaluation and development of interpretation model. The lithofacies of the rock units were grouped according to textural and structural features and grain sizes of well (E-AH1, E-BW1 and E-L1). Four different facies (A, B, C and D) were identified from the cored intervals of each well. Facies A was classified as a reservoir and facies B, C and D as a non-reservoir. Detailed petrophysical analyses were carried out on the selected sandstone interval of the studied wells. The cut-off parameters were applied on the seven studied sandstone interval to distinguish between pay and non-pay sand and all intervals were proved to be producing hydrocarbon. Volume of clay, porosity, water saturation and permeability were calculated within the pay sand interval. The average volume of clay ranged from 23.4% to 25.4%. The estimated average effective porosity ranged from 9.47% to 14.3%. The average water saturation ranged from 44.4% to 55.6%. Permeability ranged from 0.14mD to 79mD. The storage and flow capacity ranged from 183.2scf to 3852scf and 2.758mD-ft to 3081mD-ft respectively. The geological well completion reports classify these wells as a gas producing wells. E-L1 is estimated to have a potential recoverable gas volume of 549.06 cubic feet, E-BW1 is estimated to have 912.49 cubic feet and E-AH1 is estimated to have 279.69 cubic feet.